From e-Learning 1.0 to e-Learning 2.0:Threats & Opportunities for Higher Education Institutions in the Developing Countries - Kundi, G. M.; Nawaz, A. (European Journal of Sustainable Development, 2014)
The effective use of information and communication technologies (ICTs) in higher education institutions (HEIs) is a global issue for individual researchers, institutions, governments and societies as a whole. New technologies offer opportunities for the developing countries to resolve their long standing problems of national/international isolation and mass-education. Researchers are posting reports of positive results of e- Learning applications around the world; however, using digital gadgets for teaching, learning and education management is neither automatic nor devoid of challenges and problems. There are both development and use problems for the developers, users and institution. Broadly there are three e-Learning systems available to the HEIs: traditional computer-based learning, blended learning and virtual learning with relative merits and demerits but their choice is based on the availability of resources and professionalism. Most of the developing countries (DCs) have started experimenting with traditional and blended systems while developed world is practicing and researching the virtual systems. This paper is an effort to portray a picturesque of the same evolution of e-Learning from e-Learning 1.0 to e-Learning 2.0 in the HEIs of developing states like Pakistan. Critical analyses and argumentation were the research tools used for examination and analysis and to interpret the results of the analysis. Keywords: HEI, ICTs, Traditional, Blended, and Virtual e-Learning, e-Teachers, e- Students e-Administrators.